Determinação por cromotografia em fase gasosa de aminoácidos livres em salames submetidos a ultrassom - Donadel, Jossiê Zamperetti (2015)
Amino acids are organic compounds abundant in animal tissues, especially in meat and meat products, in free form or polymers, participating in biochemical reactions and may be precursors of compounds of interest in the quality control of these foods. The aim of this study was to optimize and validate a method for determination of free amino acids by gas chromatography in Italian dry fermented sausage subjected to ultrasonic bath for 3, 6 and 9 min. Free amino acids were evaluated in salami pieces fermented/seasoned (initial time), at finished product (28 days) and 120 days after manufacture. The extraction was performed using 0.1 N HCl. An aliquot of samples were subjected to vacuum drying, followed by derivatization with MTBSTFA, which has been optimized with respect to time, temperature and reaction solvents (pyridine and acetonitrile). The instrumental and chromatographic conditions of injector temperature, constant pressure and column temperature program was optimized to ensure the method selectivity and efficiency. The use of a mixture of acetonitrile/MTBSTFA in the ratio 1:1 (v/v) using a temperature of 100 °C for 2 h promoted derivatizing all L-amino acids contained in the analytical standards.The injector temperature of 320 °C and 15 psi constant pressure gave the best efficiency in mass transfer of the analytes into the column, while also providing higher resolution and accuracy. The determination coefficients obtained for amino acids were higher than 0.99, except for glycine (0.98). Fourteen amino acids showed a linear range of from 1.0 to 160.0 mg L-1 with LOD and LOQ ranged between 0.3 and 10 g ml-1 and 1 and 20 mg L-1 and inter-day coefficients of variation accurately less than 15% for most analytes.The increase in the concentrations of most amino acids was observed over time processing/storage, indicating that there was an intense proteolytic activity with the release of free amino acids. In the finished product (28 days), treatment with ultrasound affected significantly (p <0.05) concentration of some amino acids. At this point, the amino acids alanine, glycine, valine, leucine, proline and methionine (non-polar) and tyrosine (polar uncharged) showed lower concentrations to control, on the other hand there was an increase of glutamic acid and arginine. The free amino acids found in salami are important compounds because through chemical reactions of decarboxylation or deamination can be precursors of volatile compounds responsible for characteristic processed meat product flavor/aroma. Thus, the employment of no conventional analytical techniques such as gas chromatography for determination of free amino acids allows obtaining information of great importance for the quality control and product development, correlating the technological and nutritional properties with the properties sensory involving amino acids as precursors.